Accounting for a changing and uncertain climate in planning and policymaking today: lessons for developing countries - and Ranger, Nicola; Garbett-Shiels, Su-Lin (Climate and Development, 2012)
Climate change is increasingly altering the pattern of climate-related risks. Developing countries and in particular least developed countries will be among the most severely impacted by climate change. These risks can seem remote in comparison with more immediate threats and needs, but if climate change is not considered upfront in existing planning and policymaking processes today, decision makers risk locking-in future impacts that may prove irreversible or much more costly and difficult to rectify than is necessary. The challenge for planners and policymakers, explored in this paper, is that future climate conditions are deeply uncertain. Decision methods are available to tackle these problems; however, these tend to be data- and resource-intensive and therefore, difficult to routinely apply. Further, a gap in currently available guidance is the explicit link to the adaptation needs of a developing country. We discuss the implications of this development context for the priorities for adaptation and the relative allocation of efforts in adaptation. This paper focuses on the identification of adaptation options and strategies that are robust to the deep uncertainties in future climate risk, culminating in a framework of six building blocks. It takes the perspective of exploring how decisions today might be adjusted to account for uncertain and changing long-term climate risks. We suggest a core principle is to focus on promoting climate-resilient development and increasing long-term adaptive capacity while, crucially, avoiding inflexible decisions that could lock-in future climate risk or foreclose adaptation options.
Keywords: Adaptation; Climate change; Development; Planning; robustness; uncertainty